Environmental constraints on oviposition of aquatic invertebrates with contrasting life cycles in two human‐modified streams. (7th June 2013) - Alp, Maria; Indermaur, Lukas; Robinson, Christopher T.
Summary Many streams today have modified channels, substratum composition, flows and temperature regimes. Understanding how these potential stressors affect key processes governing populations is crucial towards counteracting species decline and loss. For aquatic organisms with complex life cycles that include a terrestrial adult stage, successful reproduction involving a transition from the terrestrial to aquatic environment for oviposition can be an important constraint. Our main goal was to test for the effects of local stream degradation on egg mass densities of macroinvertebrates with different requirements for oviposition habitat. We experimentally manipulated oviposition substrate availability in two Swiss gravel‐bed rivers by adding bricks to stream beds of channelised, restored and near natural reaches differing in their depth profile and availability of large rocks. We followed oviposition on bricks and natural rocks between May and October 2008 and quantified egg mass densities of two aquatic insects with a terrestrial stage (Baetis spp. and Hydropsyche spp.) and an entirely aquatic leech Erpobdella octoculata. Individual and interactive effects of mean water depth fluctuations, depth variability, frequency of large rocks and temperature on egg mass densities were evaluated using a model selection approach. Response to our manipulation in terms of relative use of bricks for oviposition was strongest in the two insect taxa, whose egg mass densities responded to the presence of large substrata in study reaches. We also found evidence for a weak water level effect on egg mass densities of Baetis, a mayfly that uses protruding rocks for oviposition, in contrast to Hydropsyche, which apparently is capable of diving. While no clear response to our manipulation was found in Erpobdella octoculata, its overall cocoon densities were influenced by the variability of depth profile and increased in reaches with lower streambed heterogeneity. Our results suggest that stream degradation has high potential to constrain reproduction of many species, in particular those with complex life cycles such as aquatic insects. Investigation in modified riverscapes of the specific effects of different constraints to recruitment processes is a prerequisite for successful management and conservation.